Parallel Graph Algorithms - Erciyes, K (Guide to Graph Algorithms, 2018)
We investigate methods for parallel algorithm design with emphasis on graph algorithms in this chapter. Shared memory and distributed memory parallel processing are the two fundamental models at hardware, operating system, programming, and algorithmic levels of parallel computation. We review these methods and describe static and dynamic load balancing in parallel computing systems.